Pengaruh Diskon dan Gratis Ongkir terhadap Keputusan Pembelian pada E-Commerce Lazada Indonesia - Hendrianto, Aris Yhoga; Kusdiyanto, Kusdiyanto (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to examine the influence of discounts and free shipping promotions on consumer purchase decisions on the Lazada e-commerce platform. This research uses a quantitative approach with a survey method, involving 155 respondents who are Lazada users in Tawangsari District. Research methodology: Data was collected using a Likert-scale questionnaire, and data analysis was performed using SmartPLS software. Results: The results show that discounts have a positive and significant effect on purchase decisions with a coefficient of 0.486 and a p-value of 0.000. Free shipping promotions also have a significant effect, with a coefficient of 0.349 and a p-value of 0.007. Conclusions: Discount offerings have a direct impact on increasing consumers' purchase intentions on the Lazada platform. Consumers are more inclined to utilize discount promotions, as they perceive a higher value relative to the cost incurred, which subsequently leads to an increase in purchase frequency. In addition, free shipping promotions significantly influence consumer purchasing decisions. The removal of shipping fees is perceived as a benefit, encouraging consumers to complete transactions without additional hesitation. Overall, both discount promotions and free shipping offers serve as effective marketing strategies in enhancing consumer purchasing decisions on Lazada's e-commerce platform. These strategies provide the company with a competitive advantage in attracting and retaining consumers within the digital marketplace. Limitations: This study is limited by several factors. First, the sample is confined to Lazada users in the Tawangsari District, which may restrict the generalizability of the findings to other regions. Contribution: In conclusion, discount and free shipping strategies are important factors that encourage consumers to make purchases on Lazada. This study provides valuable insights for e-commerce managers to optimize their promotional strategies to attract more consumers.